Cultural Criticism and Terminology "The Balconies of the North Sea" as a Model - Djerbouaa, Amel; Boumali, Hanane (Milev Journal of Research and Studies, 2021)
This research aims to dissolve the engagement between the term cultural criticism and the term cultural studies and culture criticism, by applying it to a fictional text, "The Balconies of the North Sea", and to define the epistemic boundaries for each term separately. It tracks its paths and changes in the monetary field. Highlighting the status of cultural criticism, "which is one of the most prominent literary phenomena and the most thorny topic produced by the currents of postmodern criticism.